Behavioral Systems Analysis in Understanding Models of Corruption Control. - de Almeida, Marília Pacheco; Caldas, Luíza Freitas; da Silva França, Bruna Maria Barbosa; Vasconcelos, Laércia Abreu; Sandaker, Ingunn (Behavior & Social Issues, 2024)
Poverty reduction and prosperity sharing are among the goals of international organizations for promoting sustainable development. One obstacle to achieving this goal is the spread of corruption. To decrease it, anticorruption strategies have prevailed around the world, and different practices have been implemented to eliminate or mitigate this problem. Applied behavior analysis (ABA) has also investigated small- and large-scale corruption behaviors. However, a systemic approach is required to better understand the contingencies of corruption. A complementary approach between behavior analysis's (BA) different principles, fields, and tools is helpful in promoting the continuous and dynamic improvement of the mechanisms used in understanding anticorruption practices. This article combines BA basic principles, behavioral systems analysis (BSA), and the total performance system (TPS) conceptual tool to better understand how anticorruption agencies, described as role models, have acted in the face of corruption. In particular, it highlights how the World Bank Group's Sanctions System and the National Disciplinary Board of the Brazilian Office of the Comptroller General offer contributions to international organizations, banks, and public institutions in developing efficient and effective systems for corruption mitigation. In addition to the practical contributions learned through the analysis of the anticorruption agencies' behavioral systems, this research proposes adding the institutional multiplicity term to BSA's and TPS's literature and the concept of culturo-behavioral hypercycles to the studies on corruption mitigation.